Are they stress-free? Examining stress among primary school teachers in Tanzania - Kavenuke, Patrick Severine; Kayombo, Joel Jonathan; Kinyota, Mjege (CEPS journal, 2022)
Teachers enter the profession with enthusiasm for the new adventure. Unfortunately, when they start working, they encounter circumstances that give rise to stress. The present study, which used a sample of 550 participants from 50 primary schools selected from the Kisarawe district in the Coastal Region of Tanzania, examines the extent of stress among primary school teachers and the factors influencing stress. Overall, the results indicate that teachers' levels of stress range from low to moderate. Moreover, the results from hierarchical regression analysis indicate that factors such as sex, class size, age, career intentions and teaching subject significantly predict teachers' stress. The study concludes that there is a need for the government, policymakers and school administrators to reduce teachers' workload. Furthermore, school administrators in particular should be supportive and should design mechanisms that could develop a sense of collegiality among teachers in order to improve teacher-to-teacher relationships. (DIPF/Orig.)